A plantwide control proposal for ethylbenzene production - Victor Dias Veloso; Anamaria de Oliveira Cardoso (The Journal of Engineering and Exact Sciences)
In the present article, a plantwide control structure is proposed for the benzene alkylation process. The mathematical model used in the simulations developed in scilab free software, version 6.1, was based on previous studies. Initially, operational restrictions were evaluated and possible controlled variables were chosen based on operational objectives and tested by performing step disorders to validate the criteria. The choice of the best pairs was made through the RGA (Relative Gain Array) relative gain matrix. The structural decisions adopted and the results obtained through computational simulation indicated that although there are interactions between the control loops, the possible pairs, T1-FR2 and T4-Q4, minimize the system interactions. The adjusted parameters of the controller were effective in controlling the disturbance, presenting little or no overshoot with satisfactory ascent and response times. The control structure adopted with the PID controller is just one of the fundamental steps within the plantwide control methodology and shows the controller’s ability to meet the proposed structural objectives.